The effectiveness of using feedback instruments for assessing writing short stories in a tenth grade group from CINDEA Judas, in the third school district at Dirección Regional de Educación of Puntarenas, during the second school term, 2020 = La efectividad en el uso de instrumentos de retroalimentación para la evaluación de la escritura de cuentos cortos en un grupo de décimo año del CINDEA Judas del Circuito 03 de Puntarenas, durante el segundo periodo del 2020 - González González, Isaac 1997- (2021)
This study reports on the effectiveness of using feedback instruments for assessing the writing skill of tenth grade students using short stories. This action research study followed a mixed methodology. The participants were 11 students ages 15 to 42, in a tenth-grade group from CINDEA Judas in the third school district at Dirección Regional de Educación of Puntarenas, during the second school term of 2020. The main objective of this research was to examine the possible effectiveness of implementing feedback instruments for assessing writing skills with a sample population through the creation of short stories. Interestingly, the researchers found that 73% of students (8 learners) improved their writing proficiency at the end of the fieldwork stage. The results obtained revealed that the use of feedback instruments is effective in upgrading a learner´s writing mastery. For instance, 55% of the participants were able to increase their vocabulary repertoire. Also, for the final result, 45% of the students gained satisfactorily outcomes and 55% of the learners improved their scores in their grammar insights showing a marked improvement compared to the diagnostic test results. Finally, the researchers concluded that through the implementation of feedback instruments using short stories strategies EFL learners can improve their writing skills more effectively. Lastly, it is recommended that MEP authorities train their language instructors in the use of this pedagogical strategy.